Permeability of compacted soils - Kek, Hardy Yide (2014)
More than two-thirds of Singapore’s land area are covered with residual soils. Residual soils are often compacted and used for engineering construction works due to its favourable engineering properties. Compacted soils are by nature unsaturated. Unlike saturated soils, permeability of unsaturated soils is a function of void ratio and degree of saturation.